Characterization of the cytotoxic effects of the combination of cisplatin and flavanol (-)-epicatechin on human lung cancer cell line A549. An isobolographic approach - Varela-Castillo, O.; Cordero, P.; Gutiérrez-Iglesias, G.; Palma, I.; Rubio-Gayosso, I.; Meaney, E.; Ramirez-Sanchez, I.; Villarreal, F.; Ceballos, G.; Nájera, N. (Experimental Oncology, 2018)
Background: Among malignancies, lung cancer is a leading cause of death. Platinum-based therapeutic compounds used to treat lung cancer have not been able to increase the survival of patients and such compounds have a high incidence of adverse and toxic effects. It has been proposed that flavonoids such as catechins may significantly reduce the risk of developing cancer, alongside with other health benefits. The aim of this work was to determine the effect of (-)-epicatechin, the main flavanol found in cocoa, on the proliferation of the lung non-small cell adenocarcinoma cancer cell line A549, and to determine its effects when added simultaneously with cisplatin. Materials and Methods: Concentration-response curves for cisplatin and epicatechin were obtained, inhibitory concentrations calculated and an isobolographic analysis was then performed. Results: We found that epicatechin has a concentration-dependent inhibitory effect on proliferation of tumor cells and the isobolographic analysis reveals that the effect of its combination with cisplatin is synergistic. It was also observed that epicatechin promotes cell death by apoptosis. Conclusions: Epicatechin might be considered for future studies to explore its possible use as coadjuvant in cisplatin-based treatments.